ҚАРАҚАЛПАҚСТАН ОЙКОНИМЛЕРИНИҢ ЖАСАЛЫЎЫ - Қурбанов, М.Д. (FAN va JAMIYAT, 2024)
The article analyzes general and various aspects of toponym formation and word formation. In toponymy, specific aspects of onomastic conversion, transonymization and composition are studied.